IDENTIFYING SCHIZOPHRENIA USING INDIRECT CHARACTERIZATION OF THE MAIN CHARACTER IN LOVE FOR A DEAF REBEL - Andhika Arla Putra; Ingatan Gulo (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
In this article, the writers discuss one of the psychological issues called as schizophrenia. This study aims to describe schizophrenia on Pearl as the main character in Love for a Deaf Rebel novel through indirect characterization and to see whether the main character suffered from paranoid schizophrenia as it claimed in the novel or suffered from the other types of schizophrenia instead. To answer the research questions, the writers used psychological approach because this study discussed about psychological aspects of character called schizophrenia which is faced by the main character in the novel. The theories that the writers applied are schizophrenic theory and character and characterization. Moreover, this study applied qualitative descriptive method because this study intends to investigate an issue in form of words. Overall, the writers conclude that Pearl as the main character exhibits the symptoms and characteristics of more than one type of schizophrenia. Three out of five types of schizophrenia were found in Pearl through indirect characterization. Keywords: Indirect characterization, psychological approach, schizophrenia